Proceedings of the 6th International Conference on Automotive User Interfaces and Interactive Vehicular Applications 2014
DOI: 10.1145/2667317.2667322
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis on the NHTSA Acceptance Criteria for In-Vehicle Electronic Devices

Abstract: We tested a commercial in-car navigation system prototype against the NHTSA criteria for acceptance testing of in-vehicle electronic devices, in order to see what types of in-car tasks fail the acceptance test and why. In addition, we studied the visual demands of the driving scenario recommended by NHTSA for task acceptance testing. In the light of the results, NHTSA guidelines and acceptance criteria need to be further developed. In particular visual demands of the driving scenario and for different simulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The 85 th percentile as a threshold is a common design standard in traffic engineering; the Alliance Guideline also (2006) used 85 th percentile to define the border between a reasonably distracting task and an unreasonably distracting task. It is largely unaffected by outliers compared to 100 th percentile, or the maximum, and so provides a robust estimate of noisy data (Kujala, Lasch, & Mäkelä, 2014). Thus, using 85 th percentiles for different aspects of glance patterns, as well as the sampled population, supports the argument that a task complying with these criteria poses reasonable risk for a large majority of the population.…”
Section: Introductionmentioning
confidence: 63%
“…The 85 th percentile as a threshold is a common design standard in traffic engineering; the Alliance Guideline also (2006) used 85 th percentile to define the border between a reasonably distracting task and an unreasonably distracting task. It is largely unaffected by outliers compared to 100 th percentile, or the maximum, and so provides a robust estimate of noisy data (Kujala, Lasch, & Mäkelä, 2014). Thus, using 85 th percentiles for different aspects of glance patterns, as well as the sampled population, supports the argument that a task complying with these criteria poses reasonable risk for a large majority of the population.…”
Section: Introductionmentioning
confidence: 63%
“…The participant sample validation by using their occlusion distances driven during an occlusion trial ensure that the driver sample includes both, "short-glancers" and "long-glancers". This validation is an important part of the testing method since previous studies have indicated that drivers have individual off-road glance duration tendencies [2,16] and these individual differences in glance durations could affect the results of the distraction testing [3,23].…”
Section: Methodsmentioning
confidence: 99%
“…Driver performance data are known to be highly variable both within and between human test participants, and from site-to-site using identical test protocols, for indeterminate reasons (27), or even at the identical site with identical tasks but different participants (8)(9)(10). Using relative rather than absolute criteria for task assessment, as in the Alliance's Principle 2.1B (5), and as required in the ISO Detection Response Task standard (27), eliminates a large source of such variability, thus increasing repeatability of a given acceptance test result.…”
Section: Additional Limitations Of Nhtsa Guidelines' Test Protocol and Teort Criterionmentioning
confidence: 99%
“…Aust et al found that "long glancers" represent about one-sixth of the population, so if enough long glancers happen to be randomly selected in a study sample, all tested tasks will exceed the LGP or MSGD criterion, or both criteria (8). Kujala et al conducted a test of 10 secondary tasks with the Guidelines glance criteria (9). All tasks met the MSGD and LGP criteria, but one of the three tasks that did not meet the TEORT criterion was "find road number," where it was a matter of chance if the participant happened to look at the display when the road number was present.…”
mentioning
confidence: 99%
See 1 more Smart Citation